Adjusting Astigmatism. - Gallop, Steven (Optometry & Visual Performance, 2020)
All optometrists are taught how to prescribe lenses to maximize acuity, particularly distance acuity. The standard approach is to prescribe for maximum acuity based strictly on the measurements, in particular Snellen findings, keratometry, and subjective refraction. Prescribing in this way is perhaps considered most important when faced with astigmatism. There is much more to the visual process than visual acuity. In fact, visual acuity is probably the least important...certainly the least consequential aspect of the visual process. A case study describes a unique approach to managing the refractive status of a young patient with habitual cylinder lenses and a complex visual profile.